Dengue and COVID‐19, overlapping epidemics? An analysis from Colombia. Issue 1 (11th July 2020) - Cardona‐Ospina, Jaime A.; Arteaga‐Livias, Kovy; Villamil‐Gómez, Wilmer E.; Pérez‐Díaz, Carlos E.; Katterine Bonilla‐Aldana, D.; Mondragon‐Cardona, Álvaro; Solarte‐Portilla, Marco; Martinez, Ernesto; Millan‐Oñate, Jose; López‐Medina, Eduardo; López, Pio; Navarro, Juan‐Carlos; et al.
Abstract: Coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has rapidly spread throughout Latin America, a region swept by multiple previous and ongoing epidemics. There are significant concerns that the arrival of COVID‐19 is currently overlapping with other viruses, particularly dengue, in various endo‐epidemic regions across South America. In this report, we analyzed trends for both viral infections in Colombia during the first 20 epidemiological weeks (EWs) of 2020. From 1st January to 16th May 2020 (EWs, 1‐20), a total of 52 679 cases of dengue and 14 943 cases of COVID‐19 have been confirmed in Colombia. As both conditions may potentially lead to fatal outcomes, especially in patients with chronic co‐morbidities, overlapping infections, and co‐occurrence may increase the number of patients requiring intensive care and mechanical ventilation. In regions, such as Valle del Cauca, intensified preparation for such scenarios should be pondered, and further studies should be performed to address this critical issue in a timely matter. Highlights: Overlap between COVID‐19 and endemic diseases, such as Dengue, in certain regions, such as Latin America, is a mattern of concern. In Colombia during the first 20 epidemiological weeks of 2020, a total of 52, 679 cases of dengue and 14, 943 cases of COVID‐19 have been confirmed. Both conditions may potentially lead to fatal outcomes, especially in patients with chronic co‐morbidities. COVID‐19 and dengue together may increase the number of patients requiring intensive care and mechanical ventilation. Further studies should be performed to address this critical issue in a timely matter.